Dietary organic acids ameliorate high stocking density stress-induced intestinal inflammation through the restoration of intestinal microbiota in broilers - Dai, Dong; Qi, Guanghai; Wang, Jing; Zhang, Haijun; Qiu, Kai; Han, Yanming; Wu, Yuanyuan; Wu, Shugeng (Journal of animal science and biotechnology, 2022)
BackgroundHigh stocking density (HSD) stress has detrimental effects on growth performance, intestinal barrier function, and intestinal microbiota in intensive animal production. Organic acids (OA) are widely used as feed additives for their ability to improve growth performance and intestinal health in poultry. However, whether dietary OA can ameliorate HSD stress-induced impaired intestinal barrier in broilers remains elusive. In this study, a total of 528 one-day-old male Arbor Acres broilers were randomly allocated into 3 treatments with 12 replicates per treatment including 10 birds for normal stocking density and 17 birds for HSD. The dietary treatments were as follows: 1) Normal stocking density + basal diet; 2) HSD + basal diets; 3) HSD + OA.ResultsHSD stress can induce increased levels of serum corticosterone, lipopolysaccharides, interleukin-1β, tumor necrosis factor-α, and down-regulated mRNA expression of ZO-1, resulting in compromised growth performance of broilers (P < 0.05). Dietary OA could significantly reduce levels of serum corticosterone, lipopolysaccharides, interleukin-1β, and tumor necrosis factor-α, which were accompanied by up-regulated interleukin-10, mRNA expression of ZO-1, and growth performance (P < 0.05). Moreover, OA could down-regulate the mRNA expression of TLR4 and MyD88 to inhibit the NF-κB signaling pathway (P < 0.05). Additionally, HSD stress significantly decreased the abundance of Bacteroidetes and disturbed the balance of microbial ecosystems, whereas OA significantly increased the abundance of Bacteroidetes and restored the disordered gut microbiota by reducing competitive and exploitative interactions in microbial communities (P < 0.05). Meanwhile, OA significantly increased the content of acetic and butyric acids, which showed significant correlations with intestinal inflammation indicators (P < 0.05).ConclusionsDietary OA ameliorated intestinal inflammation and growth performance of broilers through restoring the disordered gut microbial compositions and interactions induced by HSD and elevating short-chain fatty acid production to inhibit the TLR4/NF-κB signaling pathway. These findings demonstrated the critical role of intestinal microbiota in mediating the HSD-induced inflammatory responses, contributing to exploring nutritional strategies to alleviate HSD-induced stress in animals.